Cutting-Edge Delivery Systems and Adjuvants in Tolerogenic Vaccines: A Review - Chiara Puricelli; Elena Boggio; Casimiro Luca Gigliotti; Ian Stoppa; Salvatore Sutti; Roberta Rolla; Umberto Dianzani (MDPI AG, 2022)
Conventional therapies for immune-mediated diseases, including autoimmune disorders, transplant reactions, and allergies, have undergone a radical evolution in the last few decades; however, they are still not specific enough to avoid widespread immunosuppression. The idea that vaccine usage could be extended beyond its traditional immunogenic function by encompassing the ability of vaccines to induce antigen-specific tolerance may revolutionize preventive and therapeutic strategies in several clinical fields that deal with immune-mediated disorders. This approach has been supported by improved data relating to the several mechanisms involved in controlling unwanted immune responses and allowing peripheral tolerance. Given these premises, several approaches have been developed to induce peripheral tolerance against the antigens that are involved in the pathological immune response, including allergens, autoantigens, and alloantigens. Technological innovations, such as nucleic acid manipulation and the advent of micro- and nanoparticles, have further supported these novel preventive and therapeutic approaches. This review focuses on the main strategies used in the development of tolerogenic vaccines, including the technological issues used in their design and the role of "inverse adjuvants". Even though most studies are still limited to the preclinical field, the enthusiasm generated by their results has prompted some initial clinical trials, and they show great promise for the future management of immune-mediated pathological conditions.